2005
DOI: 10.2140/gt.2005.9.1043
|View full text |Cite
|
Sign up to set email alerts
|

Singular Lefschetz pencils

Abstract: We consider structures analogous to symplectic Lefschetz pencils in the context of a closed 4-manifold equipped with a "near-symplectic" structure (ie, a closed 2-form which is symplectic outside a union of circles where it vanishes transversely). Our main result asserts that, up to blowups, every near-symplectic 4-manifold (X, ω) can be decomposed into (a) two symplectic Lefschetz fibrations over discs, and (b) a fibre bundle over S 1 which relates the boundaries of the Lefschetz fibrations to each other via … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

7
289
0

Year Published

2006
2006
2023
2023

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 90 publications
(296 citation statements)
references
References 15 publications
7
289
0
Order By: Relevance
“…We will present our version of this construction in Remark 6.2 at the end of the paper. Note here that the exceptional divisors are not sections of the BLF, and that the round 1-handle singularities do not all project to parallel copies of the equator, so this does not quite recover the main result of [4]. However, this construction may be sufficient as input into Perutz's program to construct smooth invariants from BLFs.…”
mentioning
confidence: 97%
See 2 more Smart Citations
“…We will present our version of this construction in Remark 6.2 at the end of the paper. Note here that the exceptional divisors are not sections of the BLF, and that the round 1-handle singularities do not all project to parallel copies of the equator, so this does not quite recover the main result of [4]. However, this construction may be sufficient as input into Perutz's program to construct smooth invariants from BLFs.…”
mentioning
confidence: 97%
“…This theorem can be compared to work of Auroux, Donaldson and Katzarkov [4] and of Etnyre and Fuller [12]. In the first it is shown that if X 4 has a near-symplectic form (which it does when b C 2 > 0), then X 4 is a broken Lefschetz pencil (BLP).…”
mentioning
confidence: 98%
See 1 more Smart Citation
“…This choice of c corresponds to the choice made in the construction of periodic Floer homology; see [15]. In this case, for any other z c 2 H 2 .X I ‫/ޒ‬ evaluating positively on the fibers of f , z ƒ h;z c and ƒ h;z c are obviously algebras over ROEkerhc 1 .s h /; i D z ƒ h;˙c 1 .s h / , so if hc 1 .s h /; fiberi ¤ 0 we have a well defined group HF.Y; F; h;˙c 1 .s h /; I z ƒ h;z c /, where the sign at the front of˙c 1 .s h / is chosen to make its evaluation on the fiber positive.…”
Section: Coefficient Ringsmentioning
confidence: 99%
“…In [35], Perutz uses and extends constructions similar to this in order to construct a "Lagrangian matching invariant" for the singular Lefschetz fibrations constructed in Auroux-Donaldson-Katzarkov [1] (which exist on blowups for any 4-manifold with b C > 0, though it is not known whether Perutz's invariant is independent of the choice of singular Lefschetz fibration on a given 4-manifold), and conjectures that this new invariant, too, agrees with the Seiberg-Witten invariant. [17] to be the homology of a chain complex CP .…”
Section: Cobordismsmentioning
confidence: 99%